Herpes Simplex Virus Type 1 Neuronal Infection Triggers the Disassembly of Key Structural Components of Dendritic Spines - Acuña-Hinrichsen, Francisca; Covarrubias-Pinto, Adriana; Ishizuka, Yuta; Stolzenbach, María Francisca; Martin, Carolina; Salazar, Paula; Castro, Maite A.; Bramham, Clive R.; Otth, Carola (Frontiers in Cellular Neuroscience, 2021)
Herpes simplex virus type 1 (HSV-1) is a widespread neurotropic virus. The primary infection in facial epithelium leads to retrograde axonal transport to the central nervous system (CNS) where it establishes latency. Under stressful conditions, the virus reactivates, and new progeny is transported anterogradely to the primary site of infection. In late stages of neuronal infection, axonal damage is known to occur. However, the impact of HSV-1 infection on morphology and functional integrity at earlier stages of infection in neuronal dendrites is unknown. Previously, we demonstrated that acute HSV-1 infection in neuronal cell lines selectively enhances the expression of Arc protein - a major regulator of long-term synaptic plasticity and memory consolidation, known for being a protein-interaction hub in the postsynaptic dendritic compartment. Thus, HSV-1 induced Arc may alter the functionality of the infected neurons having a negative impact on dendritic spine dynamics. In this study we demonstrated that HSV-1 infection causes structural disassembly and functional deregulation in cultured cortical neurons, altering protein homeostasis with intracellular accumulation of Arc, and decreased expression of spine scaffolding-like proteins such as PSD-95, Drebrin and CaMKIIβ. Our findings reveal progressive deleterious effects of HSV-1 infection on excitatory neuronal synapse function and dendritic morphology, supporting the thesis of the infectious origin of neurodegenerative processes.